2017
DOI: 10.1038/s41467-017-01216-w
|View full text |Cite
|
Sign up to set email alerts
|

The circular RNA circBIRC6 participates in the molecular circuitry controlling human pluripotency

Abstract: Accumulating evidence indicates that circular RNAs (circRNAs) are abundant in the human transcriptome. However, their involvement in biological processes, including pluripotency, remains mostly undescribed. We identified a subset of circRNAs that are enriched in undifferentiated human embryonic stem cells (hESCs) and demonstrated that two, circBIRC6 and circCORO1C, are functionally associated with the pluripotent state. Mechanistically, we found that circBIRC6 is enriched in the AGO2 complex and directly inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
237
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(249 citation statements)
references
References 44 publications
12
237
0
Order By: Relevance
“…Interestingly, like MBL, QKI might dimerize to facilitate circularization (Teplova et al, 2013). In addition, the splicing factor ESRP1 mediates circularization of circBIRC6 (derived from the baculoviral IAP repeatcontaining 6 gene) by binding to specific sites that are present in the introns flanking the circularizable exon (Yu et al, 2017). In addition, the splicing factor ESRP1 mediates circularization of circBIRC6 (derived from the baculoviral IAP repeatcontaining 6 gene) by binding to specific sites that are present in the introns flanking the circularizable exon (Yu et al, 2017).…”
Section: Sequence-vs Protein-driven Exon Circularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, like MBL, QKI might dimerize to facilitate circularization (Teplova et al, 2013). In addition, the splicing factor ESRP1 mediates circularization of circBIRC6 (derived from the baculoviral IAP repeatcontaining 6 gene) by binding to specific sites that are present in the introns flanking the circularizable exon (Yu et al, 2017). In addition, the splicing factor ESRP1 mediates circularization of circBIRC6 (derived from the baculoviral IAP repeatcontaining 6 gene) by binding to specific sites that are present in the introns flanking the circularizable exon (Yu et al, 2017).…”
Section: Sequence-vs Protein-driven Exon Circularizationmentioning
confidence: 99%
“…Hence, biogenesis of circRNA results in reduced synthesis of mRNAs from the same locus. Later works identified other RNA-binding proteins (RBPs) that regulate exon circularization in different systems and organisms; these include adenosine deaminases acting on RNA (ADAR), quaking (QKI), FUS, nuclear factors NF90/NF110, DExH-Box helicase 9 (DHX9), epithelial splicing regulatory protein 1 (ESRP1), and serine/arginine (SR)-rich proteins (Conn et al, 2015;Ivanov et al, 2015;Kramer et al, 2015;Rybak-Wolf et al, 2015;Aktas et al, 2017;Errichelli et al, 2017;Li et al, 2017a;Yu et al, 2017). Several groups identified requirements for splicing and circularization of exons and demonstrated that circularization signals are located within the introns flanking the circularizable exons (Jeck et al, 2013;Ashwal-Fluss et al, 2014;Liang & Wilusz, 2014;Wang et al, 2014;Zhang et al, 2014;Ivanov et al, 2015;Rybak-Wolf et al, 2015;Starke et al, 2015;Veno et al, 2015;Sun et al, 2016;Zhang et al, 2016b).…”
mentioning
confidence: 99%
“…Deciphering the mechanisms that how SSC functions has important implications for understanding male infertility and its treatment by controlling self‐renewal and differentiation of SSCs. In recent years, it has become clear that serval types of ncRNAs, involving miRNA, lncRNA, piRNA, small nucleolar RNA, and circRNAs, play important roles in stem cell self‐renewal by forming complicated epigenetic regulatory networks together with other epigenetic factors related to DNA methylation, histone methylation, and acetylation (Dupuis‐Sandoval, Poirier, & Scott, ; S. Hu & Shan, ; Rojas‐Rios, Chartier, Pierson, & Simonelig, ; C. Y. Yu et al, ; Z. Yu, Li, Fan, Liu, & Pestell, ). As for SSCs, although a large number of ncRNAs have been screened as potential regulatory molecules for SSC self‐renewal using high‐throughput RNA sequencing and bioinformatics approaches, only a small portion of them have been validated and functionally characterized using biological experiment to uncover roles in SSCs self‐renewal, particularly lncRNAs, piRNA, and circRNAs (K. Hu et al, ; Li et al, ; X. Li, Ao, et al, ), thus there is an urgent need to reveal more ncRNAs associated with SSC self‐renewal to elucidate the molecular mechanisms underlying SSC self‐renewal.…”
Section: Resultsmentioning
confidence: 99%
“…Gu et al () further revealed that specific lncRNAs and circRNAs might function as competitive endogenous RNAs (ceRNAs) to promote PDLSC osteogenic differentiation and periodontal regeneration by identifying differentially expressed lncRNAs, circRNAs, and mRNAs during osteogenic differentiation of PDLSCs and integrating the competitive lncRNA–circRNA–miRNA–mRNA regulatory networks. In ESCs, C. Y. Yu et al () identified a subset of circRNAs that are enriched in undifferentiated human ESCs (hESCs) and demonstrated that two, circBIRC6 and circCORO1C, could suppress hESC differentiation by directly interacting with miR‐34a and miR‐145, both of them are known to modulate target genes that maintain pluripotency. As for SSCs, Dong, Li, Qing, Huang, and Li () revealed a total of 15,996 circRNAs were identified in human testis using high‐throughput sequencing and 14,033 (87.7%) circRNAs were mapped to 5,928 host genes, involving several genes required for SSC self‐renewal, such as STK31, suggesting the potential role of circRNAs in SSC self‐renewal.…”
Section: Ncrna In Sscs Self‐renewalmentioning
confidence: 99%
“…Several studies have demonstrated that circRNAs are abundant in the stem cells and can act as a molecular “sponge” to regulate the characteristics and differentiation of the stem cells . As reported by Yu et al, circBIRC6 competitively binds to miR‐34a and miR‐145 and is involved in the regulation of stem cell pluripotency in the embryonic stem cells. A few reports described a role played by circRNAs in physiological processes of MSCs.…”
Section: Introductionmentioning
confidence: 96%